Descriptive study on malignant otitis externa in diabetic patients at a tertiary care hospital at Madurandhagam - Thirumalaipriya, V.; Madanagopal, R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Malignant otitis external (MOE) is a destructive infection, principally affecting ageing diabetic patients. The present study directed for analysing various forms of clinical presentations, causative organisms and management of such diseases. Methods: We conducted a descriptive study of patients with MOE in the ENT Department of Karpaga Vinayaga Institute of Medical College and Hospital, Madurandhagam. Haematological, biochemical and epidemiological parameters were taken and result analysis was carried out. Results: They affect both the soft tissue and bones of immunocompromised patient’s predominantly diabetic patients. Various forms of clinical presentations such as ear discharge which proved to be due to Pseudomonas aeruginosa. Facial nerve involvement, osteonecrosis and bony erosion was noted in MOE patient. Conclusions: MOE or external otitis progressing necrosis is a serious infection of the subject often older and diabetic by P. aeruginosa.